Implementation of the Corporate Social Responsibility Program of Bank Nagari Padang Panjang Branch in Providing Educational Scholarships - Monica Permata Ardi; Nazirwan Nazirwan; Fera Mutia (LPPM Universitas Ekasakti, 2025)
This study examines the implementation of a corporate social responsibility (CSR) scholarship program delivered by a regional bank branch in Padang Panjang, Indonesia, with a focus on delivery processes and governance quality. Using a qualitative case study design, data were collected through semi-structured interviews with program implementers and scholarship recipients, supported by observation and document review. Results show a six-stage implementation pathway—socialization, nomination/registration, verification, approval, disbursement, and reporting—yet governance weaknesses concentrate at two points: verification and reporting. The program operates under a stable annual budget envelope, creating recurring coverage–intensity trade-offs and increasing reliance on discretionary prioritization. Over time, a shift from mediated cash distribution to account-based transfers improved administrative traceability, but reporting remains partly aggregated, limiting recipient-level auditability and weakening transparency and accountability. The study contributes by framing CSR scholarships as governance-dependent interventions rather than simple philanthropic transfers and demonstrates how multi-actor fragmentation and resource constraints shape targeting accuracy. Practical implications include establishing standardized eligibility verification, clarifying decision rights across actors, and institutionalizing traceable reporting routines to strengthen fairness, legitimacy, and impact credibility.